Eleven rings the soul of success - Jackson, Phil. (New York Penguin Audio, 2013)
This is the story of a preacher?s kid from North Dakota who grew up to be one of the most innovative leaders of our time. In his quest to reinvent himself, Jackson explored everything from humanistic psychology and Native American philosophy to Zen meditation. In the process, he developed a new approach to leadership based on freedom, authenticity, and selfless teamwork that turned the hypercompetitive world of professional sports on its head.
Keywords: Jackson, Phil